123k views
3 votes
Proving summation without using induction

I don't understand the part after (r-1)(ar ... ) and so on, where did (r-1) go?

Proving summation without using induction I don't understand the part after (r-1)(ar-example-1

2 Answers

0 votes

Answer:

plz see the other answer w/ corrections below

Explanation:

4th row should instead be: r*Sk - Sk = ar^(k+1) - ar^0

(r-1)Sk = ar^(k+1) - a

Sk = (ar^(k+1) - a) / (r-1)


User Jughead
by
5.4k points
6 votes

Answer:

hope it can help you

k,i=0 ∑ a
r^(i) =
S_(k)


Proving summation without using induction I don't understand the part after (r-1)(ar-example-1
User Brenna
by
6.5k points